Multibeam bathymetry raw data (Kongsberg EM712 working area dataset) of RV MARIA S. MERIAN during cruise MSM98 - Gaide, Stefanie; Römer, Miriam (PANGAEA, 2021)
During the RV Maria S. Merian cruise MSM98, which took place between 2021-01-08 to 2021-01-23 bathymetry data based on multibeam echosounder (MBES) was recorded. The main objective of the cruise was focused on the hydrocarbon fluid emissions in the German North Sea and focused on the 'Entenschnabel'- area. During MSM98 the newly detected gas emissions were investigated in detail regarding its quantities, temporal and spatial variability, source and fate. Description of the data source: During the RV MARIA S. MERIAN the hull-mounted KONGSBERGER EM712 multibeam echosounder systems was used in the areas of interest. This Multibeam echosounder is operating between 40 – 100 kHz and optimal range between 12 to 1200 m water depth. With a transducer configuration of 0.5° by 0.5° (TX/RX) this system has 256 beams with up to 400 soundings in high density mode, measuring both bathymetry and backscatter. The water column data (WCD) was recorded in a separate file to detect and analyse anomalies in the water column at seep sites. Throughout the surveys, the system was set to an opening angle of 65˚ to reduce the outliers in the outer beams. The beam spacing was set to high-density equidistant mode. The ping mode was set to very shallow. Due to the fact that the priority was the detection of water column anomalies the frequency was set to 40 kHz. During bad weather, the pitch stabilization and the yaw stabilization were turned on to receive a better data quality. During the MSM98 the EM712 failed a few times (acquisition software) and therefore had to be restarted, otherwise, the system operated flawlessly during the entire cruise. The C-Keel also worked without problems during the entire cruise.
Keywords: Bathymetry; Multibeam Echosounder